HIV/AIDS: ANÁLISE EPIDEMIOLÓGICA EM UM HOSPITAL UNIVERSITÁRIO - Moraes, Mariana de Oliveira; Figueirêdo, Bárbara Camboim Lopes de; Menezes, Fábio Henrique Peixoto; Bronze, Jéssica Liberato; Araújo, Taime Victor Lima de (Gep News, 2019)
Trabalho premiado em PRIMEIRO LUGAR - Modalidade Pôster